Implementation of Motion and Song Play Methods for Early Childhood Emotional Social Development at KB Al Wafa’ Sari Village - Nining Sariwati; Syafruddin; Masitah (al-Afkar, Journal For Islamic Studies, 2024)
The aim of this research is to describe the implementation of the movement and song play method on children's social emotional development and to find out the obstacles teachers face in overcoming the implementation of the movement and song play method on the social emotional development of early childhood at Al Wafa' KB Sari Village. This type of research uses a descriptive qualitative research approach. Meanwhile, the subjects in this research were teachers and school principals. With data collection techniques using observation, interviews and documentation. The results of the research show that the implementation of movement and song play methods in Al-Wafa' Kindergarten involves activities imitating duck movements, dancing, playing angklung, clapping while singing and gymnastics. When doing the movements and songs, the children were very enthusiastic in following the movements exemplified by the teacher, some children even asked to repeat the songs and movements. Apart from that, there is also interaction between children and their friends. When the child makes a mistake, the other friends always help the child to justify his movements, the child also seems to be able to express his emotions. The obstacles faced by teachers in implementing the movement and song play method at Al-Wafa' Kindergarten in Sari Village are the lack of preparation from teachers in controlling super active children, diverse student behavior, lack of focus of children in participating in song and movement play activities. , lack of teacher understanding in terms of applying movement and song methods and lack of teaching aids (media).